Peningkatan Literasi Hukum dan Etika Komunikasi Digital bagi Masyarakat dalam Menghadapi Penyebaran Informasi di Media Sosial - Rendy Renaldy; Poppy Suryanti; M. Harviend Gilang P (ABDI AKOMMEDIA : JURNAL PENGABDIAN MASYARAKAT, 2026)
The rapid development of digital technology and social media has significantly transformed the way people communicate, access information, and participate in public discourse. However, this development has also increased the spread of misinformation, hoaxes, hate speech, defamation, and other unethical forms of digital communication. Limited public understanding of legal aspects and ethical principles in digital interaction often leads to irresponsible information sharing and potentially harmful online behavior. This community service program aimed to improve public literacy regarding digital law and communication ethics in responding to the dissemination of information on social media. The program was implemented through educational counseling, interactive discussions, and case-based learning activities designed to enhance participants’ awareness and practical understanding. The results showed an improvement in participants’ knowledge of the legal consequences of digital actions, the importance of verifying information before sharing, and the application of ethical communication in online environments. Participants also demonstrated greater awareness of responsible social media use and the need to maintain respectful and lawful digital interactions. Overall, this program contributed to strengthening community capacity in addressing information dissemination on social media in a more critical, ethical, and legally responsible manner.